(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
As a new ubiquitous network, Internet of Things (IoT, for short) is widely used in various fields, which has a huge network, diverse sensor nodes, multifarious communication protocol. The resource management in IoT is difficult and the application fields are also expanding. Meanwhile, complexity, uncertainty and ambiguity of IoT also contribute toward the development direction of â€œcomprehensive cognitionâ€, â€œintelligent decisionâ€, so the introduction of cognitive elements into the IoT to constitute Cognitive Internet of Things (CIoT, for short) is particularly important. In allusion to the possible negative packets forward problem of selfish nodes in CIoT, we proposed a multi-domain cooperation dynamic incentive mechanism based on reputation in CIoT (C2R, for short). According to the characteristics of CIoT and the QoS requirements of the users, dynamic reputation evaluation between nodes is used to achieve the self-management of the network and motivate selfish nodes to forward packets. Meanwhile, multi-domain cooperative idea expands the application scope. The simulation results show that the mechanism can better enhance the network availability, and has a good performance in packets loss and throughput.